A Public Role for the Private Sector : Industry Self-Regulation in a Global Economy - Haufler, Virginia, 1957- (Book collections on Project MUSE., 2001)
Increasing economic competition combined with the powerful threat of transnational activism are pushing firms to develop new political strategies. Over the past decade a growing number of corporations have adopted policies of industry self-regulation-corporate codes of conduct, social and environmental standards, and auditing and monitoring systems. A Public Role for the Private Sector explores the phenomenon of industry self-regulation through three different cases-environment, labor, and information privacy-where corporate leaders appear to be converging on industry self-regulation as the appropriate response to competing pressures. Political and economic risks, reputational effects, and learning within the business community all influence the adoption of a self-regulatory strategy, but there are wide variations in the strength and character of it across industries and issue areas. Industry self-regulation raises significant questions about the place of the private sector in regulation and governance, and the accountability, legitimacy and power of industry at a time of rapid globalization.